Vitamin B12 Ameliorates the Pathological Phenotypes of Multiple Parkinson's Disease Models by Alleviating Oxidative Stress - Yue Wu; Zhongting Zhao; Naidi Yang; Chenqi Xin; Zheng Li; Jiajia Xu; Bo Ma; Kah-Leong Lim; Lin Li; Qiong Wu; Changmin Yu; Chengwu Zhang (MDPI AG, 2023)
Parkinson's disease (PD) is the second most common neurodegenerative disease characterized by progressive loss of dopaminergic neurons in the substantia nigra of the midbrain. The etiology of PD has yet to be elucidated, and the disease remains incurable. Increasing evidence suggests that oxidative stress is the key causative factor of PD. Due to their capacity to alleviate oxidative stress, antioxidants hold great potential for the treatment of PD. Vitamins are essential organic substances for maintaining the life of organisms. Vitamin deficiency is implicated in the pathogenesis of various diseases, such as PD. In the present study, we investigated whether administration of vitamin B12 (VB12) could ameliorate PD phenotypes in vitro and in vivo. Our results showed that VB12 significantly reduced the generation of reactive oxygen species (ROS) in the rotenone-induced SH-SY5Y cellular PD model. In a Parkin gene knockout C. elegans PD model, VB12 mitigated motor dysfunction. Moreover, in the 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced mouse PD model, VB12 also displayed protective effects, including the rescue of mitochondrial function, dopaminergic neuron loss, and movement disorder. In summary, our results suggest that vitamin supplementation may be a novel method for the intervention of PD, which is safer and more feasible than chemical drug treatment.